Desenvolvimento de capacidades din??micas a partir de sistemas de gest??o ambiental: um estudo em organiza????es militares da marinha do Brasil - Maranh??o, Romero de Albuquerque (2016)
Environmental issues and the principles of sustainable development have become important in the strategic management of the organization, because they generate a decisive impact on products, processes and organization as a whole. The literature suggests that the implementation or adoption of environmental practices in organizations can trigger the cycle of Dynamic Capabilities. The objective of this research was to identify and analyze the evidence and Dynamic Capabilities of elements related to the implementation of the Environmental Management System in military organizations. The method used was the case study in the Navy of Brazil, and research began with an exploratory study at the Base Naval de Val-de-C??es, which served as a reference for the definition and development of the project, then the investigation was complemented by two analyzes in other military organizations. The results show that the Environmental Management Systems implemented in Military Organizations have a strategic approach, based on internal rules of the Senior Management Naval and environmental policies in line with the trajectory of the organization. From the analyzes carried out and results obtained, it was found that each organization has capabilities related to the Environmental Management System, but not all can be considered dynamic. In this context, they will be dynamic those capabilities that will be decisive to change the organization's relationship with the environment and in this study we found: the Management and Results Control; Continuing training of employees; the enhancement of sustainable culture; and the use of water and energy practices. Periodic audits; selection of suppliers; and the selection of cooperatives can be considered Standard capabilities.